Reduced in vivo hepatic proteome replacement rates but not cell proliferation rates predict maximum lifespan extension in mice. Issue 1 (6th November 2015) - Thompson, Airlia C. S.; Bruss, Matthew D.; Price, John C.; Khambatta, Cyrus F.; Holmes, William E.; Colangelo, Marc; Dalidd, Marcy; Roberts, Lindsay S.; Astle, Clinton M.; Harrison, David E.; Hellerstein, Marc K.
Summary: Combating the social and economic consequences of a growing elderly population will require the identification of interventions that slow the development of age‐related diseases. Preserved cellular homeostasis and delayed aging have been previously linked to reduced cell proliferation and protein synthesis rates. To determine whether changes in these processes may contribute to or predict delayed aging in mammals, we measured cell proliferation rates and the synthesis and replacement rates (RRs) of over a hundred hepatic proteins in vivo in three different mouse models of extended maximum lifespan (maxLS): Snell Dwarf, calorie‐restricted (CR), and rapamycin (Rapa)‐treated mice. Cell proliferation rates were not consistently reduced across the models. In contrast, reduced hepatic protein RRs (longer half‐lives) were observed in all three models compared to controls. Intriguingly, the degree of mean hepatic protein RR reduction was significantly correlated with the degree of maxLS extension across the models and across different Rapa doses. Absolute rates of hepatic protein synthesis were reduced in Snell Dwarf and CR, but not Rapa‐treated mice. Hepatic chaperone levels were unchanged or reduced and glutathione S‐transferase synthesis was preserved or increased in all three models, suggesting a reduced demand for protein renewal, possibly due to reduced levels of unfolded or damaged proteins. These data demonstrate that maxLS extension in mammals is associated with improved hepatic proteome homeostasis, as reflected by a reduced demand for protein renewal, and that reduced hepatic protein RRs hold promise as an early biomarker and potential target for interventions that delay aging in mammals.